Actores sociales y ordenamiento territorial rural : los corregimientos de Medellín, Colombia (2014)
ABSTRACT: Urban pressure on the five corregimientos rural zones that depend administratively on a city) of Medellin have been increasing in the last years due to land demands for residential, industrial, and services developments from the city. In this paper we present the final results of a social maps analysis that were done by groups of people who inhabit these areas transitioning from urban to rural. After a brief overview on the public policies of territorial management through the last decade and using them as a central element, the paper deals with the way social actors that inhabit, interact and intervene the territory are perceived from the corregimientos. Supported on over twenty interviews we approach the social framework from three different variables: ideological position or strategy, symbolic or organizational power, and influence of each social actor on the topic being analyzed.